Cost Effective Video Integration within an Electrophysiology Laboratory - Zakutney, Timothy J.; Cleland, Mark J.; Foch, Santiago (CMBES Proceedings, 2010)
The Electrophysiology (EP) Laboratory is one of the most complex procedure rooms operating in a cardiovascular institution. Treatment of cardiac arrhythmias requires a strong reliance on several medical devices and technology. In particular, the availability of information from physiological monitoring, fluoroscopy, echocardiography, and auxiliary systems, during the EP procedure is crucial to aid in medical decision making. The University of Ottawa Heart Institute constructed its second EP Lab in January 2009. The research and education to be performed in this laboratory required a functional, flexible, expandable, and cost-effective solution for video integration. The Department of Biomedical Engineering (BME) worked closely with the all stakeholders to plan, design, and install a low cost solution that allowed flexible control of video information. A needs analysis was performed to identify all sources of information. Schematics of electrical, infrastructure, and cabling requirements were then created. Discussions with vendors helped to identify components, devices, and final configurations of the system. The final design allowed the centralization of all computer hardware into one area thus clearing valuable real estate within the laboratory allowing for an efficient and adaptable space. Flexibility is built in the system to facilitate the switching of key video signals to allocated monitors. As a cost effective alternative to “turnkey” solutions from manufacturers, the same integration devices and electronics achieve the same result and performance at a vastly reduced cost. This method for integration can easily be extended to the catheterization laboratory, operating room, hybrid rooms, and other patient care areas.